2005
DOI: 10.7589/0090-3558-41.4.810
|View full text |Cite
|
Sign up to set email alerts
|

First Report of an Intraerythrocytic Small Piroplasm in Wild Iberian Lynx (Lynx pardinus)

Abstract: A wild injured Iberian lynx (Lynx pardinus) was taken from the Sierra Morena population. During the health check small intraerythrocytic piroplasms, morphologically indistinguishable from other feline piroplasms, were observed in Wright-Giemsa-stained blood films. Amplification by polymerase chain reaction of a portion of the 18S nuclear small subunit (NSS) rRNA gene and sequencing revealed similarity of the unknown organism with sequences obtained from Pallas's cat from Mongolia and from a domestic cat in Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 9 publications
3
47
0
Order By: Relevance
“…The absence of positive results in samples from Doñ ana agrees with the previous study of Luaces et al (2005), who did not detect the piroplasm in any of the 47 samples from this area. The 3 parasitized lynxes were sampled in summer.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of positive results in samples from Doñ ana agrees with the previous study of Luaces et al (2005), who did not detect the piroplasm in any of the 47 samples from this area. The 3 parasitized lynxes were sampled in summer.…”
Section: Discussionsupporting
confidence: 91%
“…Cytauxzoon felis causes a generally highly fatal disease in domestic cats in the USA, with wild felids such as the bobcats ( Lynx rufus ) and pumas ( Puma concolor ) as the main reservoirs for this pathogen [35]. However, other species of Cytauxzoon infecting wild or domestic felids outside America have been described, including C. manul , molecularly characterized from a Pallas’ cat ( Otocolobus manul ) from Mongolia [36, 37], and genetically-close Cytauxzoon sp., reported in wild felids and domestic cats from Spain, France, Portugal and Italy [11, 22, 23, 25, 27, 3841]. Information on the epidemiology and clinical manifestations of infection of domestic cats by other species distinct from C. felis is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, Cytauxzoon sp. infects the Iberian lynx ( Lynx pardinus ) and wildcats ( F. s. silvestris ) [27, 3840]. Due to the extremely low population size of the Iberian lynx, it has been suggested that most likely, the natural reservoir for Cytauxzoon sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three of these genera contain species of veterinary concern and Cytauxzoon spp. are increasingly reported in domestic and wild felid species worldwide (Luaces et al, 2005;Criado-Fornelio et al, 2004;Peixoto et al, 2007;Ketz-Riley et al, 2003). The Cytauxzoon spp.…”
Section: Introductionmentioning
confidence: 99%